Spatial distribution and possible origin of the high velocity lower crust in the northern margin of the South China Sea - Jih-Hsin Chang; Zih-Lin Hong; Arif Mirza; Liang-Fu Lin; Hsien-Hsiang Hsieh; Justin Yen-Ting Ko; Sung-Ping Chang; Chin-Yeh Chen; Ting-Yi Liu (Geoscience Letters)
Abstract High-velocity lower crust (HVLC) near the continent–ocean transition zone is significant for recording magmatic activity and early rifting history and is likely to be sourced from various types of magma supplies, including passive decompression melting, hot mantle plume, active small-scale mantle convection, and fertile source mantle. In the northern margin of the South China Sea (composed of the Dongsha Passive margin to the west and the SW Taiwan active margin to the east), a large amount of geophysical data, including refraction seismic data, enable us to prepare a map of the thickness distribution of the HVLC and estimate its volume. After revisiting published data, the volume of the HVLC in the northern margin of the South China Sea is found to be comparable but slightly less than that in continental large igneous provinces such as the Deccan Trap of west-central India or oceanic plateaus such as the Shatsky Rise in the northwest Pacific Ocean, probably indicating that they may have similar active source origins. Based on a more feature-based analysis (h–v p diagram; a scatter plot showing mean velocity of lower crust versus corresponding crustal thickness) to identify the source of the underplating material in a magma-involved margin, we tentatively suggest that the HVLC along the Dongsha passive margin showing no h–v p correlation is most likely dominated by small-scale mantle convection of the Peikang–Dongsha mantle convection cell, and the HVLC along the SW Taiwan active margin showing a negative h–v p correlation is more likely to be dominated by the pre-existing distal domain of the continental margin. We propose that rather than being dominated by a hot mantle plume, small-scale mantle convection may be more likely to be responsible for the opening of the South China Sea, and suggest that a more inclusive geodynamic model to reconcile geophysical and geochemical observations should be further investigated.